Voting on Embryonic Stem Cell Research: Citizens More Supportive than Politicians - David Stadelmann; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2016)
As the public debate over stem cell research continues, the observable voting behaviour in Switzerland offers a unique opportunity to compare the voting behaviour of politicians with that of voters. In this paper, by analysing the outcomes of a referendum on a liberal new bill regulating such research, we reveal an almost 10 percentage point lower probability of the bill being accepted by politicians than by a representative sample of voters. Whereas the politicians' behaviour is driven almost entirely by party affiliation, citizen votes are driven not only by party attachment but also by church attendance. Seldom or never attending church increases the probability of bill acceptance by over 23 percentage points, while supporting the Christian Democratic Party makes supporting the bill less likely for voters, suggesting that religious observance is important. The observance of these tendencies in Switzerland – an environment that promotes discussion through direct democratic rights – strongly suggests that citizens see the benefits of stem cell research.
Keywords: D72; I10; 330; Representation; Stem Cells; Innovation